Long-term outcome of catheter ablation for atrial fibrillation in patients with severe left atrial enlargement and reduced left ventricular ejection fraction. Issue 11 (17th September 2021) - Demarchi, Andrea; Neumann, Laura; Rordorf, Roberto; Conte, Giulio; Sanzo, Antonio; Özkartal, Tardu; Savastano, Simone; Regoli, François; Vicentini, Alessandro; Caputo, Maria Luce; Klersy, Catherine; Petracci, Barbara; et al.
Abstract: Aims: Data regarding the efficacy of catheter ablation in heart failure patients with severely dilated left atrium and reduced left ventricular ejection fraction (LVEF) are scanty. We sought to assess the efficacy of catheter ablation in patients with reduced LVEF and severe left atrial (LA) enlargement, and to compare it to those patients with preserved left ventricular function and equally dilated left atrium. Methods and results: Three patient groups with paroxysmal or persistent atrial fibrillation (AF) undergoing a first pulmonary vein isolation (PVI) were considered: Group 1 included patients with normal or mildly abnormal LA volume (≤41 mL/m 2 ) and normal LVEF; Group 2 included patients with severe LA enlargement (>48 mL/m 2 ) and normal LVEF; and Group 3 included patients with severe LA enlargement and reduced LVEF. Time to event analysis was used to investigate AF recurrences. The study cohort includes 439 patients; Group 3 had a higher prevalence of cardiovascular risk factors. LA enlargement was associated with a two-fold in risk of AF recurrence, on the contrary only a smaller non-significant increase of 30% was shown with the further addition of LVEF reduction. Conclusions: The long-term outcome of patients with severe LA dilatation and reduced LVEF is comparable to those with severe LA enlargement but preserved LVEF. Long-term efficacy of PVI is certainly affected by the enlargement of the left atrium, but less so by the addition of a reduced LVEF. CA remains the best strategy for rhythm control both in paroxysmal and persistent AF in this subgroup of patients.